Maternity waiting homes utilization and associated factors among women who gave birth in the last one year in rural settings of Basona Worena District, Ethiopia: A cross sectional study - Endale Menkir Degife; Eyosiyas Yeshialem; Abdurrahman Mahammed Ahmed; Taye Anbessie Teklemariam; Abebe Nigussie Ayel (PLoS ONE, 2025)
Background Maternal waiting home is a residence near to health centers or hospitals that can be used as a temporary house for pregnant women for several days, while waiting for delivery reached, and a few days after labor. Most of the scholars focused on assessing the intention and knowledge of mothers to utilize maternal waiting homes for their recent delivery even though ignorance of utilization. In Ethiopia, the utilization of maternal waiting homes and its associated factors among women who gave birth in rural setting were not clearly described. Objectives The overall objectives of this study were to assess maternity waiting home utilization and associated factors among women who gave birth in the last one year in the rural settings of Basona Worena District, Ethiopia, in 2024. Methods A community-based cross-sectional study was conducted in Basona worena district. Multi-stage sampling techniques were used to select 460 study participants. Structured and pre-tested interviewer-administered questionnaires were used to collect data. Data were entered to Epi-data version 4.6 and exported to SPSS version 25 software for cleaning and statistical analysis. Bivariable and multi-variable logistic regression analysis was conducted to identify the association between dependent and independent variables and strength of association was measured based AOR with 95% confidence interval. Statistical significance was declared at p-value less than 0.05. Result The overall magnitude of maternity waiting home utilization was 56.7% (95% Cl: 52.4, 61.3). In this study, family size (AOR = 2.76, 95%, CI: 1.27,5.99), government-employed women(AOR = 0.12,95%,CI:0.03,0.44),maternal age (26–30years) (AOR = 0.22,95% CI:0.08,0.65), primary level maternal education (AOR = 3.20,95%,CI:1.40,7.32), birth preparedness plan (AOR = 10.23,95%,CI:9.8,29.3), and MWH utilization plan (AOR = 6.82,95%,CI: 2.7,17.3) were significantly associated with maternity waiting home utilization. Conclusion The overall maternity waiting home utilization was 56.7%, which is relatively low compared to previous studies. Therefore, more attention is needed to improve maternal education, strengthen the birth preparedness plan, and MWH utilization plan, as well as focus high-parity women on their birth complications readiness, which accelerates maternity waiting home utilization.